Exploitation tests of an electric powertrain for a light electric vehicle - Łebkowski, A. (Scientific Journal of Gdynia Maritime University, 2017)
The paper describes the design of a light electric vehicle – MEGA eCITY. Its basic parameters and properties are discussed. During a project led by the Mielecka Agencja Rozwoju Regionalnego MARR S.A., a number of such vehicles were extensively tested in real road driving conditions and on a roller dyno. While under testing, the vehicles were remotely monitored using a system provided by the ELTE GPS company. Basing on the gathered vehicle data, an analysis of light electric vehicle MEGA eCITY was performed. In the summary of the article, the results of testing and analysis are presented.